Model Course Review Horay : Upaya Meningkatkan Hasil Belajar Matematika Bentuk Aljabar - Dangkua, Sri Rahayu; Resmawan, Resmawan; Zakiyah, Siti (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
This research aims to improve students' mathematics learning outcomes in the Algebraic Form material using the Course Review Horay learning model. This study is a classroom action research (CAR) conducted in two cycles, involving students from SMP Negeri 1 Kabila as the research subjects. Each student is considered successful if their mathematics learning outcome test meets the minimum completeness criteria, which is 75. The research results show that in the first cycle, the completeness rate was 67.86% out of 28 students, and it increased in the second cycle, with 24 students achieving a completeness rate of 85.71%. This indicates that implementing the Course Review Horay learning model is believed to improve students' mathematics learning outcomes in the Algebraic Form material.